Peranan Promosi Terhadap Penjualan pada CV. Pasir Biru Desa di Kabupaten Lebak - Ratu Neneng Rozbiati; Eris Harismasakti; Anim . (E-Journal Studia Manajemen, 2014)
This study aims to determine selling at CV. Pasir Biru Lebak Banten and to find out how much the role of promotion increasing sales. The research methods is a quantitative method, the type of survey research. Populations used are all employees of CV. Pasir Biru totaling 35 people, the sample in this study as many as 32 people. Data analysis techniques used simple linear regression analysis. The result proved that there is a positive and significant effect between the role of promotions on sales.